(untitled) (Research, Society and Development, 2021)
Health education from the perspective of interprofessionalism in Brazil takes place after a long debate on changes in higher education. Academic training from the perspective of interprofessionalism became more evident, after debates and needs in the service about comprehensiveness in health. Thus, several courses in the country have in their National Curriculum Guidelines the perspective of training aimed at collaborative practices and interprofessional training. This work, developed during the period of the Education Program for Work for Health (PET-Health) thematic axis Interprofessionality, offered subsidies to reflect on the trajectory of Physical Education, Medicine and Psychology courses at a University of Minas Gerais, in a articulation process for curriculum integration focusing on Interprofessional Education for the Unified Health System. Content analysis was qualitatively carried out for the interpretation of information from the Curriculum Pedagogical Projects of the aforementioned courses. The analysis carried out showed that it is possible to integrate the curriculum between the courses, as they are all located in the progressive field. The implementation of actions that enable Interprofessional Education requires changes in the institutional culture, based on debate and collective reflection. The PET-Saúde Interprofessionalidade was a great agent of change and the analyzes produced allowed it to trace strategies and seek actors for curriculum integration, development of Interprofessionalism and strengthening of the Unified Health System. The analyzes of this study can also serve as a subsidy for discussion in other courses in the health area.